Corelationship of PEFR, MMF, FEF25%,FEF50%, FEF75% with Age, Height and Weight among Non Smoker Apparently Healthy Adult Male - Begum, Sharmin Ara; Kuryshi, Mohammad Syedul Alam; Begum, Momtaz; Akhter, Shahin; Jahan, Iffat (Journal of Brahmanbaria Medical College, 2026)
Background: Pulmonary functions may vary due to variations in individual age, height, weight, BMI and some other factors. Spirometric pulmonary function test is an important clinical test to assess the condition of the lung. Some previous study observed the relationship between lung functions with anthropometric parameters. So this study is aimed to find out the relation of PEFR, MMF, FEF25%, FEF50% and FEF75% withage, height and weight of adult apparently healthy non smokermale within normal BMI. Materials and methods: This study was conducted in the Department of Physiology, Chittagong Medical College, Chattogram, during January 2019 to December 2019 in collaboration with Continental Group Private Limited (Abu Baqar Ciddique) Chattogram and EPV (Energypac Power Venture) Chittagong Limited, Patiya, Chattogram. 35 apparently healthy adultnon smokermales between the ages 20-40 years, working inair conditioned environment were taken in this study. A questionnaire along with general information about previous diseases, medication and family history was filled up. Anthropometric measurements like height, weight were measured and BMI was calculated. Lung function test parameters like PEFR, MMF, FEF25%, FEF50% and FEF75% were measured by digital spirometer (Chestgraph HI-101, Japan). Pearson correlation coefficient test wasdone by using SPSS-25 for statistical analysis to see the relation of PEFR, MMF, FEF25%, FEF50% and FEF75% with age, height and weight within normal BMI. Results: Significant negative correlation were observed between PEFR and MMF with age (p<0.05) in this study. But anon significant negative correlation was observed between FEF25%, FEF50% and FEF75%with age. Significant positive correlation were observed between MMF and FEV75% with height (p<0.05) in this study. PEFR, FEF25% and FEF50% showed non significant positive correlation with height (p>0.05). Significant positive correlation were observed between MMF, FEF25% and FEV75% with weight (p<0.05) in this study. PEFR and FEF50% showed non significant positive correlation with weight (p>0.05). Conclusion: The result of this study suggest that pulmonary function is significantly decreased with advancement of age. Pulmonary function has positive correlation with height and weight within normal BMI. Journal of Brahmanbaria Med. Coll. Volume 07 Issue 02 July 2025 ; 16-21